UJI AKTIVITAS ANTIRADIKAL BEBAS EKSTRAK DIETIL ETER DAUN SIRSAK (Annona muricata Linn.) ASAL KOTA MAKASSAR DENGAN METODE DPPH - Sitti Amirah; Rahmawati Rahmawati; Andi Evi Wulandari Luspi (As-Syifaa Jurnal Farmasi, 2011)
Has been on concerning test of activity radical scavenging of soursop leaves (Annonamuricata Linn.) extract of dietileter with DPPH method. This research aimed to know the level activity of free radical based on binding of DPPH free radicals of Soursop leaves (Annonamuricata Linn.).Extraction of soursop leaves (Annonamuricata Linn.) by macerate with methanol, methanol extract then is partition with dietileter.Than measured of quantitative by five concentration  50 ppm, 100 ppm, 200 ppm, 300 ppm and 400 ppm, the result of measured have done  with statistical method of regretion simple linier with average value of IC50 are 4980,4 ppm.  This potency explainextract activity is still very lowers than vitamin C and BHT with value of IC50 are 10,304 mg/ml dan 43,394 ppm.  Key Words :DPPH, Radical scavenging, Annonamuricata Linn.